SEMARTOUR : IMPLEMENTING SMART TOURISM FOR THE FUTURE OF SEMARANG CITY TRAVEL - Tiya Dwi Rachmanti; Amron Amron; Febrianur Ibnu Fitroh Sukono Putra (Universitas Dian Nuswantoro, 2026)
The research aims to explore the benefits, challenges, and barriers associated with the adoption of smart tourism technologies in the local tourism industry. A qualitative approach was used, with purposive sampling selecting 22 key stakeholders, including destination managers, accommodation providers, technology developers, and government officials. Data were collected through in-depth interviews, participatory observation, and social media analysis. Thematic analysis was employed to interpret the findings, which revealed that “SEMARTOUR” Smart Tourism, such as location-based applications and IoT in accommodations, have significantly improved resource management and visitor satisfaction. However, challenges such as high implementation costs, limited digital infrastructure, and data security concerns remain as significant barriers. The study contributes to the growing body of knowledge on smart tourism by providing practical insights for both the tourism sector and policymakers, offering recommendations for enhancing the adoption of “SEMARTOUR” Smart Tourism in other cities.